2011
DOI: 10.1271/bbb.100444
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chlorogenic Acid Quinone and Interaction of Chlorogenic Acid Quinone and Catechins in the Enzymatic Browning of Apple

Abstract: Chlorogenic acid (CQA) is one of the major polyphenols in apple and a good substrate for the polyphenol oxidase (PPO) in apple. Apple contains catechins as well as CQA, and the role of CQA quinone and its interaction with catechins in the enzymatic browning of apple were examined. Browning was repressed and 2-cysteinyl-CQA was formed when cysteine was added to apple juice. CQA quinone was essential for browning to occur. Although catechins and CQA were oxidized by PPO, some catechins seemed to be non-enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
(19 reference statements)
3
37
0
Order By: Relevance
“…Phenolase, browning substrates (phenolic compounds), and O 2 are three important components involved in the enzymatic browning of fruit. Studies have indicated that the immediate cause of fruit browning is the enzymatic reaction of phenolic compounds . The enzymatic reaction of phenolic compounds is primarily catalysed by PPO .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolase, browning substrates (phenolic compounds), and O 2 are three important components involved in the enzymatic browning of fruit. Studies have indicated that the immediate cause of fruit browning is the enzymatic reaction of phenolic compounds . The enzymatic reaction of phenolic compounds is primarily catalysed by PPO .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that polyphenol oxidase (PPO) and phenolic compounds are key factors in the development of peel browning (PB) . Normally, the PPO and phenolic compounds separate in different cell compartments .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the browning phenomenon is usually attributed to the enzymatic reaction of the phenolic compounds, causing the formation of quinines [32][34], such as chlorogenic acid, which is oxidized to chlorogenic acid quinine by PPO. Meanwhile, peroxidase (POD) is also able oxidize a wide range of phenolic compounds to produce ortho-diquinones [35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The capability of the laccase preparations to oxidize phenols was illustrated by the kinetic investigation of some polyphenols, previously shown to be present in apple juice [28][29][30].…”
Section: Introductionmentioning
confidence: 99%